2021
DOI: 10.21037/qims-20-640
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between preoperative two-dimensional shear wave elastography and indocyanine green clearance test for prediction of post-hepatectomy liver failure

Abstract: Background: Post-hepatectomy liver failure (PHLF) is one of the most serious complications and major causes of liver resection mortality. The purpose of this study is to investigate and compare the performance of preoperative two-dimensional shear wave elastography (2D-SWE) and the indocyanine green (ICG) clearance test for the prediction of PHLF. Methods: A total of 172 consecutive patients who were undergoing major liver resection were prospectively identified. Patients were evaluated by preoperative 2D-SWE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Findings from earlier studies suggest a relevant predictive potential either at study inclusion or ICU admission: Oellerich et al [25] observed effective survival prediction in severe liver cirrhosis using ICG clearance at study inclusion. Similarly, Qui et al [26] linked ICG clearance with post-hepatectomy liver failure (PHLF), correlating the test with PHLF occurrence and severity. Ishikawa et al [27] demonstrated its predictive ability for post-operative complications in patients with hepatocellular carcinoma undergoing hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from earlier studies suggest a relevant predictive potential either at study inclusion or ICU admission: Oellerich et al [25] observed effective survival prediction in severe liver cirrhosis using ICG clearance at study inclusion. Similarly, Qui et al [26] linked ICG clearance with post-hepatectomy liver failure (PHLF), correlating the test with PHLF occurrence and severity. Ishikawa et al [27] demonstrated its predictive ability for post-operative complications in patients with hepatocellular carcinoma undergoing hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiome is considered a "hidden organ" that regulates human health, including liver function. It seems to play a complex role in the progression of liver diseases, and thus, identifying any alterations in intestinal microbial composition might help to establish novel therapeutic targets (38). Extended hepatectomy is a well-established risk factor for PHLF.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of the degrees of cirrhosis on prediction of PHLF needs to be further studied. Several predictive models of PHLF have been reported on cirrhotic patients with HCC, including the model for endstage liver disease (MELD) score, hepatic venous pressure gradient (HVPG), indocyanine green (ICG) clearance, and liver stiffness (LS) (15)(16)(17). However, all these predictive models are not effective enough in preventing deaths from PHLF in HCC patients who undergo hepatectomy with a background of cirrhosis.…”
Section: Introductionmentioning
confidence: 99%